2023
DOI: 10.1155/2023/8622525
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies on Mechanical Behavior of TIG and Friction Stir Welded AA5083 -AA7075 Dissimilar Aluminum Alloys

Abstract: Welding is a suitable and better process to manufacture complex objects for aerospace, naval, and automotive structures. Service conditions and complexity in load acting force the manufactures to make joints between dissimilar materials. Thus, there is a need for efficient welding techniques to form sound joints and an understanding of imperfections and their effects. In this study an attempt has been made to study the joining feasibility of dissimilar aluminum alloys by two different welding techniques, namel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The weld with the highest tool rotational speed (see Figure 6) exhibits the highest hardness in the nugget zone. Goriparthi et al [136], in a comparative study between TIG welding and FSW, investigate dissimilar AA5083-O and AA7075-T651 aluminum alloys at different rotational speeds (i.e., 800, 1000, 1100, 1200, and 1400 rpm) and a welding speed of 40 mm/min, with a tool characterized by a straight square pin profile. They observe that at lower rotational speed, the generated heat is not sufficient, and at higher tool rotational speeds, excessive heat causes the overflow of solidified materials and defect formation.…”
mentioning
confidence: 99%
“…The weld with the highest tool rotational speed (see Figure 6) exhibits the highest hardness in the nugget zone. Goriparthi et al [136], in a comparative study between TIG welding and FSW, investigate dissimilar AA5083-O and AA7075-T651 aluminum alloys at different rotational speeds (i.e., 800, 1000, 1100, 1200, and 1400 rpm) and a welding speed of 40 mm/min, with a tool characterized by a straight square pin profile. They observe that at lower rotational speed, the generated heat is not sufficient, and at higher tool rotational speeds, excessive heat causes the overflow of solidified materials and defect formation.…”
mentioning
confidence: 99%
“…Experienced welders often resort to a trial-and-error method when selecting parameters, but this approach might not always provide the best results. Developing an appropriate mathematical model could prevent this hit-or-miss approach by accurately predicting the outcome from a specified set of parameters [7]. This could be achieved by using differential equations that represent physical phenomena.…”
Section: Weld Quality Measuresmentioning
confidence: 99%
“…During comparative studies on TIG welding and FSW, Goriparthi et al [386] studied, inter alia, the FSW joint of 5083-O/7075-T651 alloys obtained at various TRSs (i.e., 800, 1000, 1100, 1200, and 1400 rpm) and a WS of 40 mm/min, using a tool with a straight square pin profile. They found that at lower TRSs, the generated heat was insufficient, and at higher TRSs, excessive heat induced the overflow of solidified materials and defect formation.…”
mentioning
confidence: 99%